2015
DOI: 10.1007/s12013-015-0665-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Risk Factors Associated with Recurrence and Metastasis After Radical Resection in Patients with Hepatolithiasis Complicated by Intrahepatic Cholangiocarcinoma

Abstract: The objective of this study was to analyze the predictive significance of different prognostic factors associated with recurrence and metastasis after the radical resection in patients with hepatolithiasis complicated by intrahepatic cholangiocarcinoma (HLA/IHCC). A total of 138 patients with HLA/IHCC admitted during April 2006-April 2009 were selected for this study and they were divided into two groups, with and without recurrence/metastasis. After a radical resection surgery, the patients were followed up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Tamandl et al (13) found that preoperative CA19-9 value less than 100U/ml is associated with better DFS. Zhu Y et al (14) suggests the preoperative CA19-9 can be used to determine postoperative recurrence, besides being a diagnostic indicator. In our study, the preoperative CA19-9 (≥35U/ml) was found to be related to postoperative recurrence and an independent prognostic factor affecting OS.…”
Section: Discussionmentioning
confidence: 99%
“…Tamandl et al (13) found that preoperative CA19-9 value less than 100U/ml is associated with better DFS. Zhu Y et al (14) suggests the preoperative CA19-9 can be used to determine postoperative recurrence, besides being a diagnostic indicator. In our study, the preoperative CA19-9 (≥35U/ml) was found to be related to postoperative recurrence and an independent prognostic factor affecting OS.…”
Section: Discussionmentioning
confidence: 99%
“…ICC is the second most common malignancy worldwide and accounts for 15–20% of primary liver cancer (9). Due to its rising incidence and poor prognosis, research into ICC is receiving increasing attention (10,11). Surgical resection remains one of the most effective ways to treat ICC (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have reported an increased incidence of concurrent CCA in patients with HL. [5][6][7] Hence early identification of HL-CCA is of great importance. Detection of HL-CCA is dependent on imaging modalities, such as ultrasound, CT, and MRI.…”
mentioning
confidence: 99%